Role of Islamic Banking in Turkish Financial System - Cevher, Mesut (Journal of Islamic and Religious Studies, 2018)
Within the global financial system, Islamic banks have a small but growing share, and today they have become an integral part of the global financial system. Islamic banks in the world have been operating according to interest-free financing techniques, which are mainly developed on sharing of profits and losses in accordance with the difference principles between purchase and sale. However, the presentation of financial products in Turkey is conducted by ‘participation banks’ operating according to Islamic rules. Participation banks play a vital role in economic development by gaining the unused funds to the economy. This study will examine the performance of the participation banks operating in Turkey and their increasing share in the Turkish finance sector will be assessed. The work sheet will contain three demands: First: Islamic banks and the difference between them and the definition of riba-based banks. Second: The history of Islamic banks in Turkey. Third: The role of Islamic banks in the sustainable development of the Turkish economy.